Critical Mindfulness Exploring Langerian Models - Fatemi, Sayyed Mohsen (Springer International Publishing : Imprint: Springer, 2016)
Expanding on the trailblazing ideas of Ellen Langer, this provocative volume explores the implications of critical mindfulness for making psychology more responsive and its practice more meaningful. Powerful critiques take the discipline to task for positioning therapists as experts over their clients and focusing on outcomes to the detriment of therapeutic process. Contributors use the principles of Langerian mindfulness to inform self-understanding and relationships, areas such as athletic performance and consumer decision making, and basic and complex forms of cognitive engagement. The mindfulness demonstrated here is not only critical but also creative, inclusive, and humane, with the potential to transform the consciousness of psychology and other mind-based fields. Included in the coverage: Critical mindfulness of psychology's mindlessness. The construct of mindfulness amidst and along conceptions of rationality. Understanding confidence: its roots and role in performance. Mindfulness in action: the emergence of distinctive thought and behavior. Langerian mindfulness and optimal sport performance. Health and the psychology of possibility. Critical Mindfulness is bracing and insightful reading for undergraduate and graduate students, psychologists, psychiatrists, physicians, clinicians, neurologists, and educators within and outside positive psychology. These pages challenge the wider community of professionals to rethink their perspectives on practice-as well as their long-held tenets of living.